ANALISIS PENGARUH TINGKAT SUKU BUNGA KREDIT DAN NON PERFORMING LOAN (NPL) TERHADAP PENYALURAN KREDIT USAHA MIKRO,KECIL DAN MENENGAH (UMKM) PADA BANK PERKREDITAN RAKYAT DI KALIMANTAN BARAT - B01109072, Sy. M. Yusuf (Jurnal Pembangunan dan Pemerataan, 2013)
This research discuss about the effect of Interest Rate and NPL against Small and Medium Enterprises (SME) and medium enterprises in rural banks in West Borneo. Interest Rate and NPL is one of caused factors of the size in total credit made by BPR. The purpose of this research is to find the influence of interest rates on loans and NPLs for SME. This research used a secondary data in the form of time series (time series) with 3-years study (2009-2011). The data is obtained from Indonesia Bank (IB) in West Borneo. The analysis of data is using multiple linear regression that consist of t-test, f-test and determination (R2). The results showed that interest rates have a positive and significant impact on SME of rural banks in West Borneo. However, there has no problem in high interest rates of this research, because there are other factors that are considered more profit for SME, while the result from NPL ratio has a negative and significant effect on loan at Rural banks in West Borneo. Keywords: SME Loans, Interest Rate and NPL